Experiment and numerical investigations of ultra-high toughness cementitious composite slabs under contact explosions. (January 2022) - Li, Qinghua; Chen, Bokun; Xu, Shilang; Zhou, Fei; Yin, Xing; Jiang, Xiao; Wu, Ping
Highlights: The blast tests for UHTCC slabs under different weights of charge were conducted. The existing prediction methods were employed to predict the failure modes of slabs FE model was used to simulate UHTCC slabs under blast loadings. The structured and unstructured discretizations were used in FE model. The uncertainty analysis was conducted for the input parameters in FE model. Abstract: Reinforced concrete (RC) structures under blast loading can occur severe structural damage, including cratering, spalling, and breaching. And these damages could cause danger to the personnel and equipment. In this study, ultra-high toughness cementitious composite (UHTCC) with significant strain-hardening behavior (ultimate tensile strain >3%) was utilized to improve the blast resistance of construction structure. The UHTCC square slabs with a side length of 2000 mm were tested under contact explosions. The cratering and spalling damage of slabs were investigated. A total of six slabs (three RC slabs and three UHTCC slabs) under three different weight of TNT charge (2 kg, 4 kg, and 5 kg) were tested. The results showed the UHTCC slabs presented excellent blast resistance compared with RC slabs. The existing empirical predictions were employed to explore the damage mode of UHTCC slabs compared with the experimental results. The suitability and accuracy of the predictions were discussed. The structured and unstructured discretizations with different mesh size were used in the finite element (FE) model. The simulation results from the unstructured discretizations show better agreement with the experimental results than that from the structured discretizations. The effect of mesh size on the damaged area, damaged depth, deflection-time curves of the slab and the eroded volume fraction were compared and discussed. In addition, the sensitivity analysis of input parameters in the numerical model were conducted. the maximum failure strain, the compressive strength and the mass density of UHTCC were employed as the input parameters to investigate and discuss their effects on the value of output parameters, which include the damaged area, damaged depth and maximum deflection of UHTCC slab.